Covid-19 in Central America - Calzada Olvera, Beatriz (2022)
Funding Information: A previous version of this study was originally under the UNU-WIDER project Transforming informal work and livelihoods and presented at the WIDER Development Conference ‘COVID-19 and development-effects and new realities for the Global South’, 6-8 September 2021). Publisher Copyright: © 2022 The Authors